Performance of secondary schools under different organizational dimensions - Rosales, Socorro Alkuino 1924-
The study sought to determine the relationships of selected internal organizational structures and material technology to school performance as measured by NCEE achievement, school holding power and community services as perceived by 30 principals and 292 teachers from 30 high schools in the provinces of Agusan and Butuan City. Partial correlation, t-test, Pearson Product-Moment correlation and stepwise multiple regression analysis were used. Only "intrinsic rewards" is positively associated with school performance as measured by the NCEE. Leadership significantly correlates with school performance as measured by school holding power.
Thesis (D.Ed.)--University of the Philippines, Quezon City.
Keywords: Education, Secondary -- Philippines; School management and organization -- Philippines